Design of the Argonne Low Power Reactor (ALPR) - Hamer, Eberhard E.; Grant, N. R.; Hooker, H. H.; Jorgensen, G. L.; Kann, W. J.; Lipinski, W. C.; Milak, G. C.; Rossin, A. D.; Shaftman, D. H.; Smaardyk, A.; Treshow, M.; Argonne National Laboratory. Reactor Engineering Division. (1961)
Report containing "[a] description (.) of the design of a prototype "packaged" nuclear power plant. The purpose of the plant is to alleviate fuel oil logistics and storage problems posed by remote auxiliary DEW Line radar stations north of the Arctic Circle. The ALPR (redesignated SL-1) is a 3 Mwt, heterogeneous, highly enriched uranium- fueled, natural-circulation boiling water reactor, cooled and moderated with light water. Steam at 300 psig, dry and saturated (421 deg F) is passed directly from the reactor to a conventional turbine-generator to produce electric power (300 kw nominal) and space-heating (400 kw) requirements consistent with rigid mechanical and structural specifications prescribed by the military, and dictated by the extreme geophysics prevailing at the ultimate site. The over-all design criteria emphasize: simplicity and reliability of operation and maintenance, with minimum supervision; minimum on-site construction; maximum use of standard components; limited water supply; utilization of local gravel for biological shielding; transportability by air lift; and nominal 3-year fuel operating lifetime per core loading." (p. 15)